Pengaruh Modal Usaha Dan Inovasi Produk Terhadap Keberhasilan Usaha (Studi Pada UMKM Ayam Baong) - Mila Amelia Octaviani; Deri Apriadi (Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
Ayam Baong is an F&B MSME founded by Mila Amelia Octaviani in 2017, which provides various menus focusing on crispy chicken by combining a combination of chili sauce and dry vegetables. The purpose of this study is to determine the extent of the influence of business capital and the level of product innovation on business success, both partially and simultaneously. The research method used in this study is likely a descriptive and associative method. In this study, the unit of analysis is MSME Ayam Baong Sudirman, Bandung City. The results of the study are not yet known whether there is an influence of business capital and the level of product innovation on business success at MSME Ayam Baong Sudirman, Bandung City.